Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology) - Pangan, Media (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2023)
The Front Matter of MITP, V.10 N.01, March 2023.